2018
DOI: 10.1002/jia2.25143
|View full text |Cite
|
Sign up to set email alerts
|

Maternal priorities for preventive therapy among HIV‐positive pregnant women before and after delivery in South Africa: a best–worst scaling survey

Abstract: IntroductionPregnant women newly diagnosed with HIV during pregnancy are often lost to follow up and their adherence rates drop after delivery. We quantified changes in priorities related to isoniazid preventive therapy (IPT) and antiretroviral therapy (ART) among pregnant women living with HIV.MethodsWe enrolled pregnant women recently diagnosed with HIV from 14 primary health clinics during pregnancy and followed them after delivery in Matlosana, South Africa. Best–worst scaling (BWS) was used to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…The most common preference elicitation methods used were DCE (28, 33%), CA (21, 25%), WTA (18, 21%), and WTP [including CV] (15, 18%). Only two used BWS [ 23 , 24 ], and no other preference elicitation methods were found. The oldest article was from 1998; it used WTA and WTP direct elicitations to examine women’s preferences for vaginal antimicrobial (sexually transmitted infection [STI]/HIV) contraceptives [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common preference elicitation methods used were DCE (28, 33%), CA (21, 25%), WTA (18, 21%), and WTP [including CV] (15, 18%). Only two used BWS [ 23 , 24 ], and no other preference elicitation methods were found. The oldest article was from 1998; it used WTA and WTP direct elicitations to examine women’s preferences for vaginal antimicrobial (sexually transmitted infection [STI]/HIV) contraceptives [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The two BWS studies used different types of analyses. Kim et al reported relative and mean BWS scores, paired t-tests, and linear regression [ 23 ]. Newman et al used multinomial logit and rank-exploded logit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mothers living with HIV often take ART to prevent HIV transmission to their infants at birth but may stop seeking care after safely delivering their babies [6,39]. Postpartum mothers, who already face the challenges of looking after a new baby, face a double burden by migrating [40] and being more likely to disengage from care and be lost to follow-up [4][5][6][7][8], putting them at heightened risk of adverse health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not directly ask about the benefits of preventing HIV transmission to infants, which could be the most important concern for mothers. Preventing HIV transmission to partners may pose similar social responsibility, and factors related to infants were tested in another discrete choice experiment and presented elsewhere (42) (43). Third, the an objective measure of selfreported adherence to ART, such as viral load suppression, was not available.…”
Section: Discussionmentioning
confidence: 99%